2012
DOI: 10.5897/jmer11.088
|View full text |Cite
|
Sign up to set email alerts
|

Static analysis of an isotropic rectangular plate using finite element analysis (FEA)

Abstract: This research work aims to analyze the static analysis of an isotropic rectangular plate with various boundary conditions and various types of load applications. In this paper, finite element analysis has been carried out for an isotropic rectangular plate by considering the master element as a four noded quadrilateral element. Numerical analysis (finite element analysis, FEA) has been carried out by developing programming in mathematical software MATLAB and the results obtained from MATLAB are giving good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Concluding remarks are element 189, which is the best element to perform a beam analysis rather than a 188 element and other solid elements 285. Vanam B. C. L et al [30] analyze a static analysis of a rectangular isotropic plate under different boundary conditions and load applications by finite element analysis. The results of the FEA and ANSYS (Kirchhoff plate theory) have been compared to exact solutions and showed that closed matching.…”
Section: Static Analysis Of Flat Panelmentioning
confidence: 99%
“…Concluding remarks are element 189, which is the best element to perform a beam analysis rather than a 188 element and other solid elements 285. Vanam B. C. L et al [30] analyze a static analysis of a rectangular isotropic plate under different boundary conditions and load applications by finite element analysis. The results of the FEA and ANSYS (Kirchhoff plate theory) have been compared to exact solutions and showed that closed matching.…”
Section: Static Analysis Of Flat Panelmentioning
confidence: 99%
“…where W is the applied load and r is the membrane radius. Starting from Kirchhoff's plate theory, Vanam [16] provides a model for square membrane point load deflection with the small displacement approximation of neglecting transverse shears strains:…”
Section: Experimental Data Analysismentioning
confidence: 99%
“…Actualmente esta técnica se ha utilizado en una amplia variedad de problemas, y tiene distintos enfoques para sus soluciones. (Croninl 2001;Moreno et al, 2007;Vanam et al, 2012) Roylance (2001), Pallares y Rodríguez (2009), Vélez et al (2009), exponen la importancia del uso de herramientas de simulación como el programa comercial de elementos finitos ANSYS como alternativa viable para la solución de problemas de ingeniería, ya que constituye un ejercicio de interiorización teórica y práctica de fenómenos naturales o procesos que de otra manera sería complejo explicar desde el punto de vista cuantitativo y aun cualitativo. Un software de elementos finitos como ANSYS contienen herramientas que permiten el modelado y la simulación de un gran número de fenómenos, estructuras y materiales, para lo cual divide su operación en etapas o módulos, donde generalmente se definen aspectos tales como geometría del modelo, tipos de elementos en los que se dividirá, asignación de propiedades de los materiales y generación de la malla para definir los nodos y uniones entre elementos.…”
Section: Introductionunclassified